Synthesis, characterization, and application of microporous biochar prepared from Pterospermum acerifolium plant fruit shell waste for methylene blue dye adsorption: the role of surface modification by SDS surfactant - Oraon A.; Prajapati A.K.; Ram M.; Saxena V.K.; Dutta S.; Gupta A.K. (My University, 2025)
In the present study, microporous biochar was prepared from the waste plant fruit shell of Pterospermum acerifolium. To improve porosity and nitrogen content in biochar, the powder form of the fruit shell was pre-treated by HNO3 before the biochar synthesis. Furthermore, to enhance the adsorption capacity of biochar for cationic methylene blue (MB) dye, the surface of biochar was modified by sodium dodecyl sulfate (SDS) surfactant to increase the negative charge density on the biochar surface. Before the performance of the adsorption experiments, the nitric acid-treated Pterospermum acerifolium fruit waste biochar (NAT-PABC) and SDS-modified nitric acid-treated Pterospermum acerifolium fruit waste biochar (SDS-NAT-PABC) were characterized by various sophisticated instruments such as FTIR, XRD, FE-SEM, EDX, elemental mapping, BET, XPS, and point of zero charge. An in-depth study of the functional groups and their interactions in NAT-PABC and SDS-NAT-PABC were examined with the help of the XPS technique and identified the functional groups responsible for the adsorption of MB dye. Batch adsorption experiments were carried out to determine the optimal adsorption conditions. The maximum removal percentage of MB dye was achieved at pH 10 and 9 for NAT-PABC and SDS-NAT-PABC, respectively, within 240 min. The isotherm, kinetic, and mass transfer modeling were also examined and fitted with the experimental data. According to correlation coefficient (R 2), nonlinear forms of the pseudo-second-order kinetic and Langmuir isotherm models were best suited for both NAT-PABC and SDS-NAT-PABC. The present work also reported a possible reaction mechanism that describes the adsorption phenomenon. The Gibbs energy and enthalpy for the MB adsorption process by NAT-PABC and SDS-NAT-PABC was found to be negative and positive, respectively, suggesting that the process was spontaneous and endothermic nature; therefore, the reaction was highly attainable at higher temperatures. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.